Physiology and Pathophysiology of the Biliary Tract: The Gallbladder and Sphincter of Oddi—A Review. (25th February 2013) - Behar, Jose
Abstract : The biliary tract collects, stores, concentrates, and delivers bile secreted by the liver. Its motility is controlled by neurohormonal mechanisms with the vagus and splanchnic nerves and the hormone cholecystokinin playing key roles. These neurohormonal mechanisms integrate the motility of the gallbladder and sphincter of Oddi (SO) with the gastrointestinal tract in the fasting and digestive phases. During fasting most of the hepatic bile is diverted toward the gallbladder by the resistance of the SO. The gallbladder allows the gradual entry of bile relaxing by passive and active mechanisms. During the digestive phase the gallbladder contracts, and the SO relaxes allowing bile to be released into the duodenum for the digestion and absorption of fats. Pathological processes manifested by recurrent episodes of upper abdominal pain affect both the gallbladder and SO. The gallbladder motility and cytoprotective functions are impaired by lithogenic hepatic bile with excess cholesterol allowing the hydrophobic bile salts to induce chronic cholecystitis. Laparoscopic cholecystectomy is the standard treatment. Three types of SO dyskinesia also cause biliary pain. Their pathophysiology is not completely known. The pain of types I and II usually respond to sphincterotomy, but the pain due to type III usually does not.